THE MECHANISM OF ACCOMPLISHMENT OF CONSUMER COMPLAINTS IN REVIEW AND THE IMPLEMENTATION OF CIVIL LAW IN INDONESIA - Djaja, Benny; Soewito, Rizal Iskandar (International Journal of Multidisciplinary Research and Literature, 2024)
Rapid global economic development has significantly changed the relationship between producers and consumers. This research examines the mechanism for resolving consumer complaints in Indonesia, focusing on the Consumer Dispute Resolution Agency (BPSK) and the potential for implementing Online Dispute Resolution (ODR). Data was collected through literature study, in-depth interviews, and observation. The research results show that despite a comprehensive legal framework, implementation is still hampered by lack of outreach, budget limitations, and legal inconsistencies. Many consumers do not know the existence of BPSK, so its accessibility is limited. The digital era and the development of e-commerce add complexity, with many platforms having internal complaint resolution systems that still need to be integrated with BPSK. Online Dispute Resolution (ODR) has excellent potential to improve efficiency and accessibility but is hampered by low digital literacy and inadequate infrastructure. In the financial sector, the Alternative Dispute Resolution Institution (LAPS) shows potential but requires improvements in socialization and standardization of procedures. Coordination between LAPS and BPSK needs to be improved to prevent overlapping jurisdictions. Indonesia can also learn from the best practices of other countries, such as Malaysia, to adopt a more integrated and technology-based dispute resolution system